Pengalaman orang tua anak berkebutuhan khusus dalam mendampingi pembelajaran jarak jauh selama pandemi Covid–19 - Desi Sukma Puspita Sari (Psychological Journal: Science and Practice, 2021)
The widespread prevalence of the Covid-19 pandemic has affected academics and parents alike. Due to the sudden closure of schools, students are missing out on social interactions that are essential for learning while most schools have started distance learning. It has become a tough routine for the parents working online at home as they have to ensure the education of their children. This research is descriptive qualitative research using a phenomenological approach to explore the experiences of parents who have children with special needs in accompanying distance learning during the Covid-19 pandemic. A total of 15 subjects who have children with special needs attending SLBN Pembina Malang were selected as resource persons for interviews in person (online interview). Four themes emerged from the results of data collection: (1) obstacles faced by parents; (2) the support provided by the school; (3) strategies used by parents to support learning; (4) expectations of future parents. The results of this study can be used as a reference and recommendation for educators and policymakers in the implementation of further distance learning.